Fatigue, health-related quality-of-life and metabolic changes in men treated with enzalutamide or abiraterone acetate plus prednisone for metastatic castration-resistant prostate cancer: A randomised clinical trial (HEAT). (August 2022) - Ternov, Klara K.; Sønksen, Jens; Fode, Mikkel; Lindberg, Henriette; Kistorp, Caroline; Bisbjerg, Rasmus; Faber, Jens; Klausen, Tobias W.; Palapattu, Ganesh; Østergren, Peter B.
Abstract: Introduction: Enzalutamide and abiraterone acetate plus prednisone (AAP) have similar efficacy in metastatic castration-resistant prostate cancer (mCRPC). Herein, we compare fatigue, health-related quality-of-life (HRQoL) and metabolic changes in men with mCRPC treated with enzalutamide and AAP. Materials and methods: In this single-centre, open-labelled, phase IV trial, patients with metastatic prostate cancer progressing on androgen deprivation therapy were randomly assigned to enzalutamide (160 mg daily) or AAP (1000 mg abiraterone acetate and 10 mg prednisone daily) as first-line mCRPC treatment. The primary outcome was the difference in changed fatigue (Functional Assessment of Chronic Illness Therapy-Fatigue questionnaire). The secondary outcomes were differences in changed HRQoL (Functional Assessment of Cancer Therapy-Prostate questionnaire), body composition, weight, glucose homeostasis, lipid profile and blood pressure. All outcomes were assessed at baseline and at 12-week follow-up. Trial registration: clinicaltrialsregister.eu (2017-000099-27). Results: 170 patients were randomised (1:1) to enzalutamide or AAP. The primary outcome was positive with a clinically meaningful difference in fatigue, favouring AAP (3.4 points, 95% CI 1.2; 5.6, P = 0.003). The group difference in changed HRQoL did not reach clinical significance. The most important metabolic finding was a higher increase in glycated haemoglobin (HbA1c) for AAP than enzalutamide (3.4 mmol/mol, 95% CI 2.1; 4.8, P = 0.001). Eight patients developed type 2 diabetes (T2D) in the AAP group and none in the enzalutamide group. No treatment-related serious adverse event was observed. Conclusions: AAP resulted in less fatigue than enzalutamide in a randomised setting. This was at the expense of a higher HbA1c increase and incidence of T2D. Highlights: Abiraterone results in clinically important less fatigue than enzalutamide. The treatment difference in quality-of-life favoured AAP but did not reach clinical significance. Abiraterone results in a higher incidence of type 2 diabetes than enzalutamide.